SISTEM INFORMASI PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA BERBASIS WEB (STUDI KASUS : DESA SINARANCANG) - Suwandi S.E., M.M. (Jurnal Ilmu Ekonomi dan Bisnis, 2021)
The Village Revenue and Expenditure Budget or abbreviated as APBDes every year among all village apparatus is always preoccupied with the utilization or management of village income to further be allocated to several activities aimed at developing villages. The purpose of this study was to determine how the application of the principles of transparency and accountability in the management of the Regional Budget in the Village Sinarancang Cirebon District. The main obstacles in the management of APBDes are the lack of transparency of reports, inefficient performance, inadequate reporting that hinders the implementation of village development. As an effort to overcome this problem, it is necessary to design a software application for reporting the realization of the use of web-based village budget. This transparency process did not have a positive impact on the existing governance in Sinarancang Village, as well as the government's openness in making policies unknown to the public. The implementation of the APBDes Program in Tandu Village does not apply the principle of accountability, although the application of the principle of accountability at this stage is only given to local governments. As for the community the accountability process has not been carried out until now so that until now the response from the community to support government programs is lacking. The community only wants accountability reports from the government to the community before implementing the next government program. Keywords: Information Systems, Management, Budget, village funds